Screening and diagnostic tools for complex regional pain syndrome: a systematic review. Issue 5 (May 2021) - Mesaroli, Giulia; Hundert, Amos; Birnie, Kathryn A.; Campbell, Fiona; Stinson, Jennifer
Abstract : Abstract: Complex regional pain syndrome (CRPS) is a severely painful condition that presents with a constellation of symptoms. The understanding of the pathophysiology of CRPS has evolved over time, as have the diagnostic criteria. Our primary objective was to identify screening and diagnostic tools for CRPS and summarize their feasibility, measurement properties, and study quality. A secondary objective was to identify screening and diagnostic tools used for CRPS in pediatric populations (0-21 years of age). A systematic review of English articles in electronic databases (PsycINFO, MEDLINE, Embase, CINAHL, CENTRAL, and Web of Science) was conducted with the aid of a librarian in November 2018 and updated in July 2020. Studies were included if the tool was a screening or diagnostic tool, the tool included self-report or physical examination, and the primary objective of the study was to evaluate the measurement properties or feasibility of use. For each study, data were extracted for quality indicators using the QUADAS-2 tool. No screening tools were identified. Four diagnostic tools were identified: the Veldman criteria, International Association for the Study of Pain criteria, Budapest Criteria, and Budapest Research Criteria. There are no diagnostic tools validated for use in pediatric CRPS. Because there are no extant screening tools for CRPS, all people with suspected disease should undergo rapid diagnostic assessment by a clinician. For adults, the Budapest Criteria are the preferred diagnostic tool. Future research is recommended to develop a diagnostic tool for pediatric populations and screening tools for both pediatric and adults. Abstract : Supplemental Digital Content is Available in the Text.